2016
DOI: 10.1002/chem.201600462
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Molecular Recognition of S6‐ and (SO2)6‐Corona[6](het)arenes: Control of Macrocyclic Conformation and Properties by the Oxidation State of the Bridging Heteroatoms

Abstract: We report herein the synthesis, structure, and molecular recognition of S6 - and (SO2 )6 -corona[6](het)arenes, and demonstrate a unique and efficient strategy of regulating macrocyclic conformation and properties by adjusting the oxidation state of the heteroatom linkages. The one-pot nucleophilic aromatic substitution reaction of 1,4-benzenedithiol derivatives, biphenyl-4,4'-dithiol and 9,9-dipropyl-9H-fluorene-2,7-dithiol with 3,6-dichlorotetrazine afforded S6 -corona[3]arene[3]tetrazines. These compounds u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…On the basis of nucleophilic aromatic substitution reaction, we have established highly efficient one‐pot reaction strategy and stepwise fragment coupling approach to construct corona[ n ]arenes ( n =5, 6, 8). Post‐macrocyclization chemical manipulation methods have also been developed to synthesize functional corona[ n ]arenes. Corona[ n ]arenes have been demonstrated to be versatile and fascinating host molecules to complex anions, cations, and neutral guest species …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of nucleophilic aromatic substitution reaction, we have established highly efficient one‐pot reaction strategy and stepwise fragment coupling approach to construct corona[ n ]arenes ( n =5, 6, 8). Post‐macrocyclization chemical manipulation methods have also been developed to synthesize functional corona[ n ]arenes. Corona[ n ]arenes have been demonstrated to be versatile and fascinating host molecules to complex anions, cations, and neutral guest species …”
Section: Methodsmentioning
confidence: 99%
“…Post‐macrocyclization chemical manipulation methods have also been developed to synthesize functional corona[ n ]arenes. Corona[ n ]arenes have been demonstrated to be versatile and fascinating host molecules to complex anions, cations, and neutral guest species …”
Section: Methodsmentioning
confidence: 99%
“…In fact, some cyclic thioethers having electron decient aromatic rings, and which are also analogues of thiacalix[n]arene, had been successfully prepared by a nucleophilic substitution based on this strategy. 7,8 After several attempts, we found that C S bond formation using diboromothiophene derivatives and tributyltinsul de ((Bu 3 Sn) 2 S) in the presence of Pd(PPh 3 ) 4 successfully gave thiacalix[n]thiophenes (n 4 6) (Table1). While this kind of coupling was originally developed by Kosugi and Migita in 1985 for the preparation of symmetrical/nonsymmetrical diarylsul des, 27 it was found that cyclic compounds were obtained preferentially depending on the exact conditions applied.…”
Section: Thiacalix[n]thiophenementioning
confidence: 99%
“…On the basis of nucleophilic aromatic substitution reaction, we have established highly efficient one-pot reaction strategy [8][9][10][11][12][13] and stepwise fragment coupling approach [14,15] to construct corona[n]arenes (n = 5, 6, 8). Post-macrocyclization chemical manipulation methods [9-10, 13, 14] have also been developed to synthesize functional corona[n]arenes.Corona- [n]arenes have been demonstrated to be versatile and fascinating host molecules to complex anions,c ations,a nd neutral guest species.…”
mentioning
confidence: 99%
“…Post-macrocyclization chemical manipulation methods [9-10, 13, 14] have also been developed to synthesize functional corona[n]arenes.Corona- [n]arenes have been demonstrated to be versatile and fascinating host molecules to complex anions,c ations,a nd neutral guest species. [8][9][10][13][14][15][16] Anion-p interactions are now recognized as general and useful non-covalent bond attraction force in host-guest chemistry. [17,18] To fabricate selective anion receptors on the principle of typical anion-p interactions,w er ecently prepared corona[4]arene [2]tetrazines and corona [3]arene- [3]tetrazines in which electron deficient tetrazine moieties are face-to-face paralleled and are aligned in an equilateral triangle,r espectively.…”
mentioning
confidence: 99%